The International Lender of Last Resort : How Large is Large Enought? - Jeanne, Olivier (IMF Working Papers; Working Paper ;, 2001)
This paper considers how an international lender of last resort (LOLR) can prevent self-fulfilling banking and currency crises in emerging economies. We compare two different arrangements: one in which the international LOLR injects liquidity into international financial markets, and one in which its resources are used to back domestic banking safety nets. Both arrangements would require important changes in the global financial architecture: the first one would require a global central bank issuing an international currency, while the second one would have to be operated by an "international banking fund" closely involved in the supervision of domestic banking systems.